A biomolecule chiral interface base on BSA for electrochemical recognition of amine enantiomers. Issue 7 (2nd May 2021) - Lu, Qiuna; Chen, Lei; Meng, Qi; Jiang, Yan; Xie, Licheng
Abstract: A composite chiral interface (BSA‐MB‐MWCNTs) was prepared from bovine serum albumin (BSA), methylene blue (MB), and multi‐walled carbon nanotubes (MWCNTs) for chiral recognition of amine enantiomers (1 S, 2 S )‐ N, N ′‐dimethyl‐1, 2‐cyclohexanediamine and (1 R, 2 R )‐ N, N ′‐dimethyl‐1, 2‐cyclohexanediamine. The BSA‐based composite was characterized by field emission scanning electron microscopy (FESEM) and ultraviolet–visible spectroscopy (UV–Vis). The electrochemical responses towards the two enantiomers were analyzed via cyclic voltammetry (CV), electrochemical AC impedance method (EIS), and differential‐pulse voltammetry (DPV). The experimental results showed that the combination of MWCNTs and BSA could effectively improve the overall identification efficiency, and the peak current displayed by the S ‐enantiomer is larger, indicating that the prepared chiral surface has stronger interaction with the R ‐enantiomer. Under optimized condition, the current value of the oxidation peak of the chiral modified electrode showed a good linear relationship towards the amine concentration in the range of 5.0 × 10 −3 to 5.0 × 10 −5 mmol·L −1 . The proposed electrochemical chiral interface is easy to handle and provides a promising electrochemical sensing platform that can be used to identify chiral amine enantiomers. Abstract : A composite chiral interface (BSA‐MB‐MWCNTs) was prepared from bovine serum albumin (BSA), methylene blue (MB), and multi‐walled carbon nanotubes (MWCNTs) for chiral recognition of amine enantiomers (1 S, 2 S )‐ N, N ′‐dimethyl‐1, 2‐cyclohexanediamine and (1 R, 2 R )‐ N, N ′‐dimethyl‐1, 2‐cyclohexanediamine. The peak currents difference indicates that the BSA‐modified interface has a chiral recognition effect on the enantiomer.